Heat transfer characteristics of a swirling impinging air jet emerging from a triple spiral-corrugated nozzle with a twisted tape installed - P. Eiamsa-ard; K. Wongcharee; K. Kunnarak; Manoj Kumar; Smith Eiamsa–ard; M. Pimsarn (Thermophysics and Aeromechanics, 2022)
Thermal visualization using a thermochromic liquid crystal sheet was performed to investigate and compare heat transfer behavior of a swirling impinging jet emerging from a triple spiral-corrugated nozzle with a twisted tape (SIJ with TT), a SIJ issuing through a triple spiral-corrugated nozzle, and a typical/conventional impinging jet (CIJ) emerging from a smooth straight circular nozzle. The experimental results showed that the stronger jet recirculation close to the wall due to the swirl flow created by triple spiral-corrugated nozzle and twisted tape inserts (SIJ with TT) support in reducing the value of Nusselt number between the stagnation region and surroundings. For the SIJ with TT, the average Nusselt number performed by the jets with L/dH shows that the magnitude of the heat transfer coefficient was significantly enhanced with increasing twist ratios. The maximal value Nu of the SIJ with TT was obtained at the lowest twist ratio (y/W = 2.0). This was up to 5.7 % and 35.5 % higher than those of the SIJ with TT at y/W = 4.0, and the CIJ, respectively.
Keywords: Heat Transfer Mechanisms; Fluid Dynamics and Turbulent Flows; Aerodynamics and Acoustics in Jet Flows